A Liver Biopsy Validation Pilot Study of Shear Wave Elastography, APRI, FIB-4, and Novel Serum Biomarkers for Liver Fibrosis Staging in Children With Chronic Viral Hepatitis - Rebecca Mercedes MD; Jameisha Brown PhD (C); Charles Minard PhD, MS; Cynthia M. Tsai BS; Sridevi Devaraj PHD, DABCC, FACB; Marthe Munden MD, FAIUM; Daniel Leung MD, FAASLD, FAAP (SAGE Publishing, 2020)
As liver biopsy in children poses inherent risks, noninvasive measures of liver fibrosis are needed. This was a cross-sectional, liver biopsy validation pilot study of 16 participants evaluating the ability of shear wave elastography, aspartate transaminase to platelet ratio index (APRI), fibrosis index based on the 4 factors, and novel serum biomarkers to stage liver fibrosis in children with chronic hepatitis B or C. There was very high intrasegmental shear wave speed variation in our participants and little correlation with fibrosis. APRI and monocyte chemoattractant protein (MCP-1) were higher in fibrosis stage F2-3 versus F0-1 ( P = .02, P = .06, respectively). Soluble Fas (sFas) was lower in F2-3 versus F0-1 ( P = .046). A logistic regression analysis calculated by (APRI × MCP-1)/sFas demonstrated an area under the receiver operating characteristic curve of 0.92 ( P < .001), suggesting that this combination can differentiate fibrosis stage F0-1 from F2-3 in children with chronic viral hepatitis.